2019
DOI: 10.1155/2019/6286258
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Combined Use of Ultrasonic Bone Scalpel and Hemostatic Matrix on Perioperative Blood Loss and Surgical Duration in Degenerative Thoracolumbar Spine Surgery

Abstract: How to decrease intraoperative bleeding, shorten surgical time, and increase safety in spinal surgery is an important issue. Ultrasonic bone removers and FloSeal have been proven to increase safety, reduce the surgical duration, and decrease intraoperative bleeding in skull base surgery. Therefore, we aimed to compare the surgical duration, blood loss, and complications during spinal surgery with or without the use of FloSeal and an ultrasonic bone scalpel. Therefore, we retrospectively reviewed 293 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Only one patient had recurrence of radiculopathy which was associated with iatrogenic spondylosis. Post-operative Japanese Orthopaedic Association scores were improved significantly when compared with pre-operative scores, and no patient had spinal instability and malalignment [24]. As the bone cuts have to be minimal and p r e c i s e w h i l e p e r f o r m i n g a foraminotomy, the UBS seems like a goto instrument here in our practice.…”
Section: Foraminotomymentioning
confidence: 83%
See 1 more Smart Citation
“…Only one patient had recurrence of radiculopathy which was associated with iatrogenic spondylosis. Post-operative Japanese Orthopaedic Association scores were improved significantly when compared with pre-operative scores, and no patient had spinal instability and malalignment [24]. As the bone cuts have to be minimal and p r e c i s e w h i l e p e r f o r m i n g a foraminotomy, the UBS seems like a goto instrument here in our practice.…”
Section: Foraminotomymentioning
confidence: 83%
“…There are many products in use to control bleeding such as regenerated cellulose (surgical), bipolar cautery, antifibrinolytic agents, gel foam, gelatine material (Floseal), thrombin, and fibrin glue (Tisseel). A comparative study done by Chen et al [24] showed that there is a significant difference in surgical duration and blood loss. The study showed that combined use of Floseal and UBS had led to lesser surgical duration and lesser amount of blood loss.…”
Section: Hemostasis and Surgical Durationmentioning
confidence: 99%
“…Only one patient had recurrence of radiculopathy which was associated with iatrogenic spondylosis. Postoperative Japanese Orthopaedic Association scores were improved significantly when compared with preoperative scores, and no patient had spinal instability and malalignment [26].…”
Section: Foraminotomymentioning
confidence: 87%
“…There are many products in use to control bleeding like regenerated cellulose (surgical), bipolar cautery, antifibrinolytic agents, gel foam, gelatine material (floseal), thrombin and fibrin glue (tisseel). A comparative study done by Chen et al [26] showed that there is significant difference in surgical duration and blood. The study showed that with combined use of floseal and ultrasonic bone scalpel had led to lesser surgical duration and lesser amount of blood loss.…”
Section: Haemostasis and Surgical Durationmentioning
confidence: 99%
“…In the article titled “Effects of Combined Use of Ultrasonic Bone Scalpel and Hemostatic Matrix on Perioperative Blood Loss and Surgical Duration in Degenerative Thoracolumbar Spine Surgery” [1], the IRB number was given incorrectly as (IRB201700086B0). The correct number should be (IRB201600834B0).…”
mentioning
confidence: 99%